2022
DOI: 10.1002/adma.202203900
|View full text |Cite
|
Sign up to set email alerts
|

Green Electrosynthesis of 5,5′‐Azotetrazolate Energetic Materials Plus Energy‐Efficient Hydrogen Production Using Ruthenium Single‐Atom Catalysts

Abstract: Water electrolysis involves two parallel reactions, that is, oxygen evolution (OER) and hydrogen evolution (HER), in which sluggish OER is a significant limiting step that results in high energy consumption. Coupling the thermodynamically favorable electrooxidation of organic alternatives to value‐added fine chemicals HER is a promising approach for the simultaneous cost‐effective production of value‐added chemicals and hydrogen. Here, a new coupling system for the green electrochemical synthesis of organic en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 61 publications
0
17
0
1
Order By: Relevance
“…The stability of the system was also evaluated by way of chronoamperometry, which showed that this approach exhibited considerable stability at 100 mA cm –2 with a retention rate of 95% within 45 h (Figure S18). To emphasize the advantage and potential of [Fe­(CN) 6 ] 4– -assisted PW/PB redox-coupled hydrogen production system, Figure e and Table S1 show the cell voltage, electricity consumption, and cell life of this work at a certain current density and compare it with those from different state-of-the-art seawater splitting experiments reported in the literature. , Our approach undoubtedly showed significant advantages in efficiency, energy consumption, and sustainability in H 2 production.…”
Section: Resultsmentioning
confidence: 96%
“…The stability of the system was also evaluated by way of chronoamperometry, which showed that this approach exhibited considerable stability at 100 mA cm –2 with a retention rate of 95% within 45 h (Figure S18). To emphasize the advantage and potential of [Fe­(CN) 6 ] 4– -assisted PW/PB redox-coupled hydrogen production system, Figure e and Table S1 show the cell voltage, electricity consumption, and cell life of this work at a certain current density and compare it with those from different state-of-the-art seawater splitting experiments reported in the literature. , Our approach undoubtedly showed significant advantages in efficiency, energy consumption, and sustainability in H 2 production.…”
Section: Resultsmentioning
confidence: 96%
“…[51] Qiu and co-workers synthesized 5,5'-azotetrazolate by electrooxidation of 5-amino-1H-tetrazole coupled with HER. [52] What's more, alkene oxidation can also be employed as an alternative anodic reaction coupled with cathodic HER (Figure 5f). Sargent and co-workers coupled the electrooxidation of ethylene with H 2 production to produce ethylene glycol by a gold-doped palladium catalyst in aqueous 0.1 M NaClO 4 medium.…”
Section: Coupling With Alternative Organic Chemical-based Reactionsmentioning
confidence: 99%
“…To overcome this problem, PGM-based SACs and DACs have been widely studied in HER process, such as catalysts containing Pt-, [192] Pd-, [193] Rusingle/dual atom sites. [194] For example, Yang et al trap atomic Pt in defective graphene matrix to form the Pt-C 3 configuration (named as Pt@DG, Figure 14a), which gives ultrahigh activity in HER process under both acidic and alkaline conditions. [55] As shown in Figure 14b, in acidic HER process, a much decreased overpotential (30 mV) at a current density of 10 mA cm −2 of Pt@DG is achieved compared to that of Pt/C.…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 99%